(untitled) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2015)
Introduction: We evaluated the efficacy of BacT/ALERT 3D culture medium in comparison with nested polymerase chain reaction (PCR) for early diagnosis of Mycobacterium tuberculosis (MTb) in cerebrospinal fluid (CSF). Methodology: A total of 50 clinically suspected patients with CSF findings suggestive of TBM (Tuberculous meningitis) and 20 healthy controls were included in the present study.CSF from each of the patient was inoculated in BacT/ALERT-MP culture media along with the culture on convention Lowenstein in Jensen’s medium. Simultaneously nested PCR was carried out both in CSF and growth positive above culture media targeting heat shock protein gene (hsp65), a conserved gene of MTb. Results: The culture showed 76% (38/50) positivity in TBM; however, 15% (3/20) of controls also showed false positivity by BacT/ALERT-MP system. By nested CSF-PCR, TBM could be detected in 92% (46/50)cases and 5% (1/20) in the controls. The other interesting observation was that when DNA isolated from broth of BacT/ALERT MP culture were subjected for PCR amplification, 15 (39.5%) of them yielded the desired amp icon for MTb while the broths subjected to conventional LJ media yielded for M. tuberculosis in 12 of the 38 bottles (31.5%). None of culture negative medium was positive by PCR. Sensitivity and specificity of BacT/ALERT MP culture considering all of them as real positive were 76% and 85% while for nested PCR the corresponding values were 92% and 95% respectively. Conclusions: BacT/ALERT 3D culture medium seems to be unsatisfactory as isolation sensitivity rate is very poor. Moreover, growth indicated in the medium must be confirmed for being Myco bacteria as other contaminants can also grow. DOI: http://dx.doi.org/10.3126/saarctb.v11i2.12429 SAARC J TUBER LUNG DIS HIV/AIDS, 2014;XI(2),Page: 15-20